Bovines Migration Effect on the Global Behavior of the Babesiosis-Bovine Epidemic Model - Mezouaghi, Abdelheq; Darazirar, Rassim; Djilali, Salih; Mounir, Tahar Abbes (Journal of Environmental Accounting and Management, 2026)
This study explores the impact of infected bovine immigrations on the outbreak of Babesiosis disease. A mathematical model is formulated to investigate this effect, specifically considering two cases: one with infected bovine immigration and another without it. In the first case, the immigration is assumed to occur only in bovines, excluding the tick population. The key finding of this case reveals that the epidemic remains persistent and the system admits a unique endemic equilibrium that is globally asymptotically stable. In the second case, the model assumes immigration of bovines exclusively in the susceptible and recovered populations. In this scenario, the dynamics of the model are governed by the basic reproduction number, denoted as R _0 . When R _0 1, the disease persists, and the unique endemic equilibrium is globally asymptotically stable. To further validate these findings, numerical simulations are conducted, providing additional support for the obtained results.